Концепция всеединства Вл. Соловьёва как обоснование синтеза науки, философии и религии - Смоляга, Марина Витальевна (НТУ "ХПИ", 2006)
В статье предлагается реконструкция соловьёвской концепции познания в аспекте содержащегося в ней решения проблемы целостности. Своеобразие и значение свободной теософии в полагании неэлементарной организации познавательных компонентов, выходящей за пределы как собственно философии, так науки и религии.

This article suggests a reconstruction of the Solov’ev’s concept of cognition in the light of solution of the integrity problem, that it contains. The significance and the destinctiveness of free theosophy are in the substantiation of the unelementary organizition of cognition componentry. This unelementary organization exceeds the bounds of both philosophy and religion, and science.
Keywords: познание; целостность; теософия